1,8-Cineole inhibits platelet-leukocyte aggregate formation by reducing P-selectin expression - Petry, Julie; Mai, Han; Shoykhet, Maria; Bashiri Dezfouli, Ali; Wollenberg, Barbara (Frontiers in Pharmacology, 2025)
IntroductionPlatelets, traditionally recognized for their role in hemostasis, have increasingly been implicated in cancer progression, including head and neck squamous cell carcinoma (HNSCC). Beyond releasing growth factors and chemokines, platelets modulate leukocyte-mediated proinflammatory responses and effector functions through direct or indirect contact. These processes promote tumor cell proliferation, survival, epithelial to mesenchymal transition (EMT) and extravasation. Consequently, targeting platelet-leukocyte aggregate (PLA) formation represents a promising pharmacological strategy to interfere with platelet-mediated pro-tumorigenic effects. 1,8-cineole, a plant-derived metabolite found in several botanical sources, has shown potent anti-platelet effects through modulation of the adenosine A2A receptor signaling. However, its influence on PLA formation has not been investigated.MethodsIn this study, we analyzed platelet activation and PLA formation in HNSCC patients compared to healthy donors. A co-culture system combined with blocking antibodies was employed to elucidate the mechanisms of PLA formation. Moreover, the pharmacological effects of 1,8-cineole were compared with those of conventional anti-platelet drugs.ResultsThe results revealed elevated P-selectin expression and enhanced PLA formation in HNSCC patients. PLA formation was predominantly mediated through P-selectin-PSGL-1 interactions. Ex vivo studies demonstrated that 1,8-cineole significantly reduced PLA formation by inhibiting P-selectin expression on platelets. Notably, traditional anti-platelet agents did not significantly inhibit PLA formation, despite effectively reducing platelet aggregation.DiscussionThese findings identify a pharmacological effect of 1,8-cineole in disrupting platelet-leukocyte interactions via suppression of the P-selectin-PSGL-1 axis. This suggests that 1,8-cineole offers potential pharmacological benefits in mitigating platelet-mediated inflammation and tumor progression.